HEAVY METAL CONCENTRATIONS OF Cd AND Zn IN SEAWATER AND SEDIMENT OF THE WEST COAST OF KARIMUN BESAR ISLAND RIAU ISLANDS PROVINCE - Ivan Purba; Bintal Amin; Yusni Ikhwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted from January to March 2015 by taking samples of seawater and sediment from the west coast of Karimun Besar Island of Riau Islands Province and analyzed their heavy metals concentrations. Analysis of samples was carried out in Marine Chemistry Laboratory, Faculty of Fisheries and Marine Sciences, University of Riau by using Atomic Absortion Spectrophotometer. The results showed that the highest concentrations of Cd (0.109 mg/L) and Zn (0.227 mg/L) in seawater were found in the area of the boat and harbour activities, whilst the highest concentration in the sediment samples were found for Cd in Pelawan Coast (3.664 μg/g) and Zn (6.552 μg/g) in the ferry port area. The highest organic matter in the sediment was found in the ferry port (3.82%) and the lowest was in the Pelawan Coast (0.65%). Zn concentrations in sediment were still below the range of the ERL but Cd concentration has already exeeded the ERL but still below the ERM value. Based on Potential Ecological Risk Index, Cd may cause possible negative impact on the aquatic ecology of the West Coast of Karimun Besar Island.Key Words: Heavy Metals, Water, Sediment, Karimun